Transforming Mebeler MSME Marketing in Ngempit Village Kraton Pasuruan through Digital Marketing Strategies - Mochamad Mas’ud; Siti Khoiriyah; Muhammad Sofiyulloh; Siti Ayundatus Solikha (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
The Covid-19 pandemic that occurred in Indonesia caused many problems, one of which was in the economic sector. Part of the economic sector that also feels the impact is the Micro, Small and Medium Enterprises (MSMEs) sector. Ngempit Village, Kraton District, Pasuruan Regency is one of the villages with residents whose community economic activities are partly as MSME actors. The COVID-19 pandemic has caused demand and income to decrease. This mentoring uses a service-learning approach with three main stages, namely preparation, service and evaluation. The results of the assistance through digital marketing literacy for UMKM Mebel with a service-learning approach have proven to be effective in increasing income, demand, and expanding the business reach of UMKM Mebel, thus making a positive contribution to the local economy. This mentoring initiative has also been successful in unraveling the challenges faced by UMKM Mebel entrepreneurs who struggle in finding customers.